Determination of bacterial bioaerosols in a tobacco industry - mahdi Ghasemkhani; mahsa Seyedzadeh; saeed Eshraghi (طب کار)
Background: Bioaerosols are airborne particles that with occupational and non-occupational activities generated and were found in the air. This study aimed to determination of bacterial bioaerosols in a tobacco industry. Methods: In this cross sectional study, bioaerosols were measured with standard methods and data were statistically analyzed by using SPSS software. Results: The highest mean ± SD concentration of bioaerosols to 26.5 CFU/m3 was known Gram-negative Bacillus. Also, the highest mean ± SD concentration of bioaerosols was 39±23.3 CFU/m3 in the cigarette unit. The mean maximum temperature in outdoor was 35 oC and relative humidity in packing unit was 68.7%. Conclusion: In unit cigarette due to the process of preparing and processing tobacco the mean concentration of bioaerosols were higher of other places. The results show that the concentration of bacterial bioaerosols in all places was lower of guidelines for the assessment of bioaerosols in the indoor environment ACGIH and indoor air quality aspect bacterial bioaerosols is in good condition.